2016
DOI: 10.4236/wjcmp.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Opto-Structural Properties of Silicon Nitride Thin Films Deposited by ECR-PECVD

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The dissociation of this bonds may allow the formation of new Si-N bonds with a bond energy of 3.45 eV and the release of hydrogen [49,50]. This effect has been previously observed when SiN films are subjected to thermal annealing and it is often associated with a slight increase of the bandgap of nitrogen-rich films mainly due to the structural rearrangement of the bonding configuration of the Si-N bonds, which results in a smaller refractive index and in the densification of the SiN films [51].…”
Section: Published Bymentioning
confidence: 81%
“…The dissociation of this bonds may allow the formation of new Si-N bonds with a bond energy of 3.45 eV and the release of hydrogen [49,50]. This effect has been previously observed when SiN films are subjected to thermal annealing and it is often associated with a slight increase of the bandgap of nitrogen-rich films mainly due to the structural rearrangement of the bonding configuration of the Si-N bonds, which results in a smaller refractive index and in the densification of the SiN films [51].…”
Section: Published Bymentioning
confidence: 81%
“…We fabricated the ZnO-derived nanoimprinted-texture structure with a Si-rich SiN inserted layer and evaluated the effect of the Si-rich SiN by changing the refractive index, which can be controlled by the deposition condition in plasma enhanced chemical vapor deposition [19][20][21][22][23][24]. The ZnO-derived texture is formed like a moth-eye structure using a sol-gel-type ZnO precursor.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Charifi et al [ 68 ] characterized how the ammonia to silane ratio (R = [NH 3 ]/[SiH 4 ] in the range of 0.5 to 5 influences the refractive index of SiNx layers prepared by ECR-PECVD. It was revealed that the refractive index at 633 nm increased from 1.95 to 3.35, while R was decreased from 5 to 0.5.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%